2021
DOI: 10.1186/s42506-021-00092-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of pregnant women with SARS-COV2 pneumonia: a real-life study from Egypt

Abstract: Background Knowledge about the outcome of COVID-19 on pregnant women is so important. The published literature on the outcomes of pregnant women with COVID-19 is confusing. The aim of this study was to report our clinical experience about the effect of COVID-19 on pregnant women and to determine whether it was associated with increased mortality or an increase in the need for mechanical ventilation in this special category of patients. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Zaky et al . [ 12 ] compared the outcome of COVID-19 infection on 64 Egyptian pregnant women with 114 non-pregnant women. They also reported that the two groups did not differ either in maternal complications (need for mechanical ventilation or mortality), or foetal complications (preterm labour, hydrocephalus or intrauterine foetal death).…”
Section: Discussionmentioning
confidence: 99%
“…Zaky et al . [ 12 ] compared the outcome of COVID-19 infection on 64 Egyptian pregnant women with 114 non-pregnant women. They also reported that the two groups did not differ either in maternal complications (need for mechanical ventilation or mortality), or foetal complications (preterm labour, hydrocephalus or intrauterine foetal death).…”
Section: Discussionmentioning
confidence: 99%
“…Looking back, 14 months after the '6th Workshop on Paediatric Virology', the volume of literature and data on SARS-CoV-2 and COVID-19 being published daily by the world scientific community is impressive (83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93). Since the workshop, as expected for a RNA virus, multiple variants of SARS-CoV-2 have emerged.…”
Section: Looking Back One Year Later: Developments Since the Workhopmentioning
confidence: 99%
“…To date, SARS-CoV-2 VOCs, which have been named using letters of the Greek alphabet and initially identified in various countries include Alpha (B. (89). Additional research has confirmed that vertical transmission is rare, with perinatal transmission occurring in some instances (90).…”
Section: Looking Back One Year Later: Developments Since the Workhopmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy status does not seem to increase the likelihood of COVID-19, and the majority of pregnant patients with SARS-CoV-2 infection tend to recover before the moment of giving birth [1,2]. In pregnant women infected with SARS-CoV-2, the rates of mild, moderate, and severe disease are comparable to those in the general population [3][4][5], although some data suggests that pregnant women diagnosed with COVID-19 had a higher rate of more severe complications than the general population, due to pregnancyspecific comorbidities overlapping the acute SARS-CoV-2 infection [6][7][8]. It is hypothesized that viral infections during the pregnancy period may affect the moment of delivery, determining a premature birth, fetal health, and development, as well as increasing the risk for infertility [9][10][11][12]; therefore, a probable consequence of COVID-19 infection during pregnancy, a syndrome resembling preeclampsia has been reported during the second and third trimesters, increasing the fetal health risk as well as the likelihood of giving birth prematurely [13,14].…”
Section: Introductionmentioning
confidence: 99%